Kānsưksā saphāwa wǣtlō̜m thī mo̜som tō̜ kānprap saphāp ton nai kānʻanubān phan kekhūai Khrōngkān Lūang Sango 3 sāiphan - Thimphikā Rānrō̜n (Sākhā Witthayāsāt Singwǣtlō̜m, Khana Witthayāsāt læ Thēknōlōyī, Mahāwitthayālai Rātchaphat Chīang Rāi, 2014)
Research on plantation of chrysanthemum in Chiang Rai Province, Thailand.